Innovative capacity: how to promote it. By teachers of economics and engineering of UMNG University (2015)
Nowadays university teachers play an important role generating innovative skills in their students, as they are the promoters of such knowledge. In this sense, it seeks to identify the conceptions on innovation that full time teachers of Economics and Engineering faculties of the Universidad Militar Nueva Granada (UMNG) have, and how these affect the way teachers encourage innovative processes in students. An information search was performed in indexed scientific databases on the topics of innovation and education from the point of view of the teachers. Later, virtual and face surveys were done to a total of 131 teachers of the study population. Small differences in thinking about the concepts and methodologies of the teachers of the faculties mentioned above were found, showing at the end, that there is a direct relationship between the labor paths and notions that they have developed regarding innovation. It is concluded that teachers based on their professional and work experience, considered among the best methodologies to promote innovation: the implementation of projects, case studies, being in contact with innovative entrepreneurs, and research experiences.